Pengaruh Fitur Kompetitif Mobile Legends terhadap Kepuasan Mahasiswa UNIKOM Jurusan Sistem Informasi Angkatan 2023 - Andri Sahata Sitanggang; Rafi Nurfauzi; Rafii Rabani; Luckman Tejahadikusumah; Surya Widyatama (Journal Innovation In Education, 2025)
Mobile games have emerged as one of the most popular forms of digital entertainment, attracting players from diverse backgrounds and age groups. Among them, Mobile Legends: Bang Bang has gained significant popularity due to its competitive and interactive gameplay. The presence of competitive elements such as ranking systems, leaderboards, and seasonal rewards is considered a key factor that sustains player engagement and motivation over time. This study aims to examine the influence of competitive features on user satisfaction within the context of mobile gaming. The research employed a quantitative descriptive approach, using a structured questionnaire developed from established literature on gamification and user experience. Responses were measured on a five-point Likert scale to capture player perceptions, habits, and satisfaction levels. Data analysis was conducted using descriptive statistics and correlation analysis to determine the relationship between competitive feature perception and satisfaction. The findings indicate a strong positive relationship, suggesting that well-designed competitive systems not only enhance motivation but also create meaningful and enjoyable experiences for players. These results underscore the importance of competitive elements in maintaining long-term engagement in mobile games, offering valuable insights for both developers and the gaming community